Single-species versus dual-species probiotic supplementation as an emerging therapeutic strategy for obesity - Karimi, G.; Jamaluddin, R.; Mohtarrudin, N.; Ahmad, Z.; Khazaai, H.; Parvaneh, M. (Elsevier, 2017)
Background and aim: Recent studies have reported beneficial effects of specific probiotics on obesity. However, the difference in the anti-obesity effects of probiotics as single species and dual species is still uncertain. Therefore, we aimed to compare the efficacy of single and dual species of bacteria on markers of obesity in high-fat diet-induced obese rats. Methods and results: A total of 40 male Sprague–Dawley rats were assigned to one of five groups of varying diets as follows: standard diet, high fat diet (HFD), HFD supplemented with Lactobacillus casei strain Shirota, HFD supplemented with Bifidobacterium longum and HFD supplemented with a mixture of these two bacterial species. After 15 weeks of supplementation, the animals were examined for changes in body weight, body fat, total count of bacteria in fecal, blood serum lipid profile, leptin, adiponectin and inflammatory biomarkers. Histological analysis of the liver and adipose tissue was performed and the hepatic mRNA expression levels of genes related to lipid metabolism were measured. It was found that probiotic supplementation of either B. longum or a mixture of B. longum and LcS bacteria significantly reduced weight and triglycerides in the HFD groups. Supplementation of B. longum bacteria showed better results in terms of modulating leptin level, fat mass, adipocyte size and lipoprotein lipase expression, as well as increasing adiponectin and peroxisome proliferator-activated receptors-γ expression compared to dual species of bacteria. No significant differences were observed in the total count of fecal bacteria, glucose and inflammatory biomarker levels between supplemented groups. Conclusions: B. longum supplementation in obesity was more beneficial in metabolic profile changes than the mixture species.